Moral Injury in Medical Students Witnessing Unethical Practices: Insights From A Cross-Sectional Survey - Easha Masood, Muhammad Hanzla Masood (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Background: Moral distress arises when an individual recognizes the ethically appropriate action but feels powerless to act due to institutional or psychological barriers. Though first described in palliative care, it now affects all medical fields. This study evaluates the impact of witnessing unethical practices on medical students’ resilience, burnout, and career intentions. Objectives: To identify the unethical practices encountered by medical students during clinical rotations, assess the severity of moral injury from such experiences, and examine its relationship with burnout and concerns about future careers. Method: A nationwide, convenience-based cross-sectional survey was conducted in July 2025 among undergraduate medical students who had completed clinical rotations and provided informed consent. A pretested electronic questionnaire collected demographic data and used the Moral Injury Outcome Scale (MIOS), along with measures of coping, burnout, and career impact. The MIOS includes shame-related and trust-violation subscales (scores 0–56), with severity classified as mild (14–28), moderate (29–42), or severe (43–56). Pearson’s chi-square test evaluated associations between variables. Ethical approval was obtained. Results: Of 78 responses, 67 were analyzed (mean age 22.0 ± 0.1 years; 94% female; 74.6% fourth-year students). Age positively correlated with the number of departments worked in (r = 0.36, p = 0.003). Reported unethical practices included disrespect toward patients (55.2%), discrimination (29.9%), lack of consent (19.4%), breaches of confidentiality (26.9%), aggression or care delays (38.8%), and record falsification (7.5%). Severe moral discomfort was noted in 38.8%, yet only 34.3% reported incidents. Mean shame and trust scores were 20.0 ± 8.8 and 24.0 ± 9.5, respectively; mean MIOS total score was 43.0 ± 18.3. Mild and moderate moral injury occurred in 52.2% and 16.4% of students. Witnessing unethical behavior was significantly associated with moral injury severity (χ² = 12.7, p = 0.005; Fisher’s p = 0.007), burnout (χ² = 8.95, p = 0.030), and future career concerns (r = 0.48, p < 0.001). Conclusion: These findings highlight the urgent need for reforms in clinical training environments to reduce unethical practices and protect the moral integrity of future healthcare professionals. Keywords: Moral Injury, Burnout, Medical Students